Assessing the applicability of energy storage system for plug-in hybrid traction system in rail rolling stock - Maslii, Artem; Buriakovskyi, Serhii; Antonenko, Roman; Gevrasov, Valentyn; Maslii, Andrii; Gevrasov, Valentyna (Technology center PC, 2025)
This study examines the rolling stock that currently employs or could be equipped with plug-in hybrid traction systems. Existing methodologies for selecting energy storage systems often limit their applicability, which creates certain constraints when choosing a solution for hybrid traction systems. As a result of the study, a well-founded preliminary selection of an energy storage system based on expert evaluation and the Harrington desirability function was carried out. Engaging experts in relevant fields makes it possible to obtain up-to-date information on technology development and assess whether parameters meet specific requirements. The application of methods for evaluating expert consensus provides a foundation for using the results in subsequent calculations. Harrington desirability function makes it possible to combine parameters with varying units of measurement and other differences, yielding a single value that can simplify decision-making. Using expert-derived evaluations, weighting coefficients for various parameters were calculated for the defined types of rolling stock. In the current research, three types of energy storage systems were selected for locomotives and multiple-unit rolling stock, meeting the specified conditions. These include battery, supercapacitor-based and flywheel-based storage systems, with overall desirability scores (without weighting coefficients) of 0.638, 0.636, and 0.573, respectively. Modifying the set of parameters, introducing additional constraints, and adjusting weighting coefficients in conjunction with motion optimization tasks makes it possible to adapt the methodology to the requirements for specific projects for constructing or upgrading rolling stock with plug-in hybrid traction systems.
Keywords: plug-in hybrid traction systems; energy storage system; Harrington desirability function